CHD Chromatin Remodeling Protein Diversification Yields Novel Clades and Domains Absent in Classic Model Organisms. (7th May 2022) - Trujillo, Joshua T.; Long, Jiaxin; Aboelnour, Erin; Ogas, Joseph; Wisecaver, Jennifer H.
Abstract: Chromatin remodelers play a fundamental role in the assembly of chromatin, regulation of transcription, and DNA repair. Biochemical and functional characterizations of the CHD family of chromatin remodelers from a variety of model organisms have shown that these remodelers participate in a wide range of activities. However, because the evolutionary history of CHD homologs is unclear, it is difficult to predict which of these activities are broadly conserved and which have evolved more recently in individual eukaryotic lineages. Here, we performed a comprehensive phylogenetic analysis of 8, 042 CHD homologs from 1, 894 species to create a model for the evolution of this family across eukaryotes with a particular focus on the timing of duplications that gave rise to the diverse copies observed in plants, animals, and fungi. Our analysis confirms that the three major subfamilies of CHD remodelers originated in the eukaryotic last common ancestor, and subsequent losses occurred independently in different lineages. Improved taxon sampling identified several subfamilies of CHD remodelers in plants that were absent or highly divergent in the model plant Arabidopsis thaliana . Whereas the timing of CHD subfamily expansions in vertebrates corresponds to whole genome duplication events, the mechanisms underlying CHD diversification in land plants appear more complicated. Analysis of protein domains reveals that CHD remodeler diversification has been accompanied by distinct transitions in domain architecture, contributing to the functional differences observed between these remodelers. This study demonstrates the importance of proper taxon sampling when studying ancient evolutionary events to prevent misinterpretation of subsequent lineage-specific changes and provides an evolutionary framework for functional and comparative analysis of this critical chromatin remodeler family across eukaryotes.